Surface passivation-assisted growth method of two-dimensional ultrathin non-layered material β-Bi2O3 and its application in optoelectronics
By using Bi2Se3 as an auxiliary agent during the growth of the two-dimensional non-layered material β-Bi2O3, it inhibits its vertical growth and promotes lateral growth, the problem of uncontrollable thickness during synthesis is solved, and the synthesis of ultra-thin and large-size materials is achieved, providing a solid foundation for high-performance devices.
Patent Information
- Application Number
- CN202411199466.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The prior art is difficult to balance its ultra-thin thickness and extended crystal size when synthesizing two-dimensional non-layered materials, and the growth of two-dimensional non-layered materials is challenging, limiting the exploration of its performance and device integration.
Bi2Se3 is used as an auxiliary agent, and the growth of β-Bi2O3 in the vertical direction is inhibited by vapor deposition method, and its lateral growth is promoted, thereby obtaining an ultra-thin and large-size two-dimensional non-layered material β-Bi2O3.
The synthesis of β-Bi2O3 of high-quality, ultra-thin thickness and large transverse size is achieved, solving the problem of uncontrollable thickness of non-layered materials and laying the foundation for the application of high-performance devices.
Smart Images

Figure CN119082700B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of two-dimensional non-layered materials and optoelectronic materials, and in particular relates to a surface passivation auxiliary growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 and its application in the optoelectronic field. Background Art
[0002] In recent years, two-dimensional materials have attracted increasing attention in the fields of electronics, optoelectronics, energy storage and conversion due to their excellent performance and broad application prospects. Among them, two-dimensional non-layered materials have abundant surface dangling bonds and highly active surfaces, showing superior performance, and are an indispensable extension and supplement to two-dimensional layered materials. First, the ultra-thin thickness gives two-dimensional non-layered materials excellent optical transparency, remarkable flexibility and mechanical strength, making them promising candidates for the manufacture of flexible devices. In addition, ultra-thin non-layered materials have tunable band gaps and enhanced conductivity, as well as ultra-high specific surface areas, which promote their application in high-performance electronics and optoelectronics. Therefore, the synthesis of two-dimensional ultra-thin non-layered materials has important basic research and practical technical significance.
[0003] At present, researchers have also developed some methods for synthesizing two-dimensional non-layered materials, such as salt-assisted chemical vapor deposition and spatial confinement. Although significant progress has been made in this field, there are still challenges in balancing the ultra-thin thickness and extended crystal size of non-layered materials and in the synthesis of other two-dimensional non-layered materials. This is mainly because non-layered materials have intrinsic isotropic chemical bonds in all directions, which makes their two-dimensional anisotropic growth very challenging, which in turn limits the exploration of their performance and device integration.
[0004] Therefore, a new growth method is urgently needed to promote the ultrathin growth of non-layered materials, so as to achieve the synthesis of ultrathin and large-sized non-layered materials. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a surface passivation-assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 and its application in the optoelectronic field.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a surface passivation-assisted growth method for two-dimensional ultra-thin non-layered material β-Bi2O3, comprising the following steps: using Bi2O3 as a precursor and Bi2Se3 as an auxiliary agent to obtain the two-dimensional ultra-thin non-layered material β-Bi2O3 through vapor deposition.
[0008] Preferably, the mass ratio of Bi2O3 to Bi2Se3 is 2:1.
[0009] Preferably, the vapor deposition includes the following steps: placing Bi2O3 and Bi2Se3 at the heat source center and upstream of the tubular furnace respectively, placing fluorophlogopite directly above Bi2O3, then heating to the growth temperature for crystal growth, and then cooling to room temperature to obtain the two-dimensional ultra-thin non-layered material β-Bi2O3.
[0010] Preferably, the distance between the fluorophlogopite and Bi2O3 is 4 mm.
[0011] Preferably, the fluorophlogopite further includes a pretreatment step before use; the pretreatment method is: peeling the fluorophlogopite and using the freshly dissociated surface as the crystal growth surface.
[0012] Preferably, the growth temperature is 680-750°C.
[0013] Preferably, the crystal growth time is 20-60 min.
[0014] The present invention provides a two-dimensional ultra-thin non-layered material β-Bi2O3 obtained by the surface passivation assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 described in the above technical solution.
[0015] Preferably, the thinnest thickness of the two-dimensional ultra-thin non-layered material β-Bi2O3 is 0.77 nm, and the maximum lateral dimension is 163 μm.
[0016] The present invention also provides the application of the two-dimensional ultra-thin non-layered material β-Bi2O3 described in the above technical solution in the field of optoelectronics.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects:
[0018] 1. The present invention uses Bi2Se3 as an auxiliary agent, and its Se atoms volatilized at high temperature can bond with the unsaturated Bi atoms on the surface of the β-Bi2O3 flakes, thereby passivating the surface of β-Bi2O3, inhibiting its growth in the vertical direction, and promoting lateral growth, which is conducive to obtaining ultra-thin large-sized non-layered β-Bi2O3 crystals.
[0019] 2. The preparation method provided by the present invention is efficient and convenient, with a simple device. There is no need to upgrade or modify the traditional CVD system. Ultra-thin large-sized non-layered β-Bi2O3 crystals can be obtained by simply adding Bi2Se3 sheets as an auxiliary agent during the growth process.
[0020] 3. The preparation method provided by the present invention has high controllability and can well solve the problem of uncontrollable thickness of non-layered materials, which is conducive to obtaining non-layered materials with ultra-thin thickness and large lateral size, and lays a solid foundation for the application of high-performance devices based on non-layered β-Bi2O3 crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0022] Figure 1 A schematic diagram of the positional relationship between the precursor and the auxiliary agent in the surface passivation-assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 provided by the present invention;
[0023] Figure 2 A schematic diagram of the crystal growth process of the surface passivation-assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 provided by the present invention;
[0024] Figure 3 Optical microscope images (ab) of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1, optical microscope image (c) of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 2, atomic force microscope image (d) of β-Bi2O3, Raman spectrum (e) and Raman scan of characteristic peaks (f);
[0025] Figure 4 The high-angle annular dark field scanning transmission electron microscopy image of the two-dimensional ultrathin non-layered material β-Bi2O3 prepared in Example 1 (a), the enlarged view of Figure a (b), the intensity line profile extracted from the white dashed box in Figure b (c), the selected area electron diffraction pattern of the two-dimensional ultrathin non-layered material β-Bi2O3 prepared in Example 1 (d), the atomic model of the β-Bi2O3 crystal along the (100) direction (e), the adsorption energy of Se atoms on different surfaces of β-Bi2O3 (f) and the adsorption energy of Se atoms from the internal bulk phase of β-Bi2O3 to the surface atomic layer (gh);
[0026] Figure 5 Optical microscope images of β-Bi2O3 prepared in Example 1 and Comparative Examples 1-3;
[0027] Figure 6 Schematic diagram of the structure of the photodetector prepared in Example 3 (a), IV curves at different light intensities (b), intensity-dependent responsivity and detectivity (c), EQE at different light intensities (d), IT curves at different wavelengths of light (e), and characteristic light response time curve in fast scanning mode (f);
[0028] Figure 7 Schematic diagram of the structure of the polarization-sensitive photodetector prepared in Example 4 (a), the IV curve under periodic change of polarization angle (b), the polar coordinate diagram of polarization-dependent photocurrent (c) and the polar coordinate diagram of polarization-dependent responsivity (d). DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] An embodiment of the present invention provides a surface passivation assisted growth method for a two-dimensional ultra-thin non-layered material β-Bi2O3, comprising the following steps: using Bi2O3 as a precursor and Bi2Se3 as an auxiliary agent, and obtaining the two-dimensional ultra-thin non-layered material β-Bi2O3 by vapor deposition.
[0032] The present invention adds Bi2Se3 as an auxiliary agent to inhibit the growth of β-Bi2O3 in the vertical direction and promote its lateral growth, thereby obtaining high-quality non-layered material β-Bi2O3 with ultra-thin thickness and large lateral size.
[0033] In a preferred embodiment, the mass ratio of Bi2O3 to Bi2Se3 is 2: 1. The amount of auxiliary agent Bi2Se3 used in the present invention affects the passivation effect, thereby affecting the growth behavior of β-Bi2O3. By controlling the amount of auxiliary agent used, controllable preparation of large-area ultra-thin β-Bi2O3 is achieved.
[0034] In a preferred embodiment, the Bi2O3 is in powder form, has an α-type crystal structure, and has a purity of not less than 99.999%; the Bi2Se3 is in flake form, and has a purity of not less than 99.999%.
[0035] In a preferred embodiment, the vapor deposition comprises the following steps: placing Bi2O3 and Bi2Se3 at the heat source center and upstream of a tube furnace, respectively, placing fluorphlogopite directly above Bi2O3, then heating to the growth temperature for crystal growth, and then cooling to room temperature to obtain the two-dimensional ultra-thin non-layered material β-Bi2O3. During the crystal growth process, the precursor Bi2O3 is adsorbed on the surface of fluorphlogopite to form nuclei and grow epitaxially, and the auxiliary agent Bi2Se3 is adsorbed on the exposed surface of the β-Bi2O3 flakes, inhibiting its vertical growth and promoting its lateral growth.
[0036] In a preferred embodiment, the distance between the center of the heat source and the upstream is 4 cm.
[0037] In a preferred embodiment, the distance between the fluorphlogopite and Bi2O3 is 4 mm.
[0038] In a preferred embodiment, the fluorphlogopite mica further includes a pretreatment step before use; the pretreatment method is: peeling the fluorphlogopite mica, using the freshly dissociated surface as the crystal growth surface; the size of the fluorphlogopite mica is 1cm×1cm; the tools for peeling the fluorphlogopite mica are precision tweezers and tape. The present invention uses fluorphlogopite as a substrate, which has the advantage of atomic-level flatness and is conducive to the growth of non-layered materials.
[0039] In a preferred embodiment, the fluorophlogopite is in the form of flakes and the number is 1 piece.
[0040] In a preferred embodiment, the growth temperature is 680-750° C. The present invention controls the growth temperature within the above range, which is conducive to obtaining Bi2O3 with a β-type crystal structure; at the same time, at the above temperature, the precursor and the auxiliary agent will volatilize, and then the precursor Bi2O3 is adsorbed on the surface of fluorphlogopite to form nuclei and epitaxial growth, and the auxiliary agent Bi2Se3 is adsorbed on the exposed surface of the β-Bi2O3 flakes, inhibiting its vertical growth and promoting its lateral growth.
[0041] In a preferred embodiment, the heating rate of heating to the growth temperature is 16° C. / min.
[0042] In a preferred embodiment, the crystal growth time is 20-60 minutes. In the present invention, the crystal growth time will affect the size of the final product. By controlling the crystal growth time, the controllable preparation of large-area ultra-thin β-Bi2O3 is achieved.
[0043] In a preferred embodiment, the cooling rate to room temperature is 12°C / min.
[0044] In a preferred embodiment, the vapor deposition uses Ar gas as a carrier gas for transporting gas; the flow rate of the Ar gas is 50-80 sccm.
[0045] The present invention provides a two-dimensional ultra-thin non-layered material β-Bi2O3 obtained by the surface passivation assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 described in the above technical solution.
[0046] In a preferred embodiment, the thinnest thickness of the two-dimensional ultra-thin non-layered material β-Bi2O3 is 0.77 nm, and the maximum lateral dimension is 163 μm.
[0047] The two-dimensional ultra-thin non-layered material β-Bi2O3 provided by the present invention has an ultra-thin thickness and a relatively large lateral size.
[0048] The present invention also provides the application of the two-dimensional ultra-thin non-layered material β-Bi2O3 described in the above technical solution in the field of optoelectronics.
[0049] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0050] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0051] Example 1
[0052] The surface passivation-assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 has the following specific steps:
[0053] S1. Use freshly peeled fluorophlogopite with a size of 1 cm×1 cm as the growth substrate.
[0054] S2. Use Bi2O3 powder with a purity of not less than 99.999% as a precursor and Bi2Se3 flakes with a purity of not less than 99.999% as an auxiliary agent.
[0055] S3. Weigh 60 mg of α-Bi2O3 powder and 30 mg of Bi2Se3 flakes, and place them at the heat source center and upstream of the tube furnace respectively. At the same time, place the fresh fluorphlogopite in step S1 4 mm above the Bi2O3 powder.
[0056] S4. The tube furnace was heated at a heating rate of 16°C / min, from room temperature to 700°C, and Ar gas was used as a carrier gas with a flow rate of 50 sccm.
[0057] S5. Keep the temperature at 700°C for 20 min for crystal growth, and then cool the system temperature to room temperature at a cooling rate of 12°C / min in an Ar atmosphere to obtain a two-dimensional ultra-thin non-layered material β-Bi2O3.
[0058] Figure 1 This is a schematic diagram of the positional relationship between the precursor and the auxiliary agent in the surface passivation assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 provided by the present invention, wherein the yellow is Bi2O3 powder, the green is Bi2Se3 flakes, and the pink is fluorphlogopite. Figure 1 It can be seen that the Bi2O3 powder is located at the heat source center of the tube furnace, the Bi2Se3 sheet is located upstream of the tube furnace, and the fluorphlogopite is located directly above the Bi2O3 powder.
[0059] Figure 2 A schematic diagram of the crystal growth process of the surface passivation-assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 provided by the present invention. Figure 2It can be seen that when Bi2Se3 is used as an auxiliary agent, the adsorption and growth of Bi2O3 in the vertical direction can be inhibited, making it more inclined to adsorb and grow along the lateral direction, which is conducive to obtaining ultra-thin Bi2O3.
[0060] Figure 3 The optical microscope images (ab) of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1, the optical microscope image (c), atomic force microscope image (d), Raman spectrum (e) and Raman scan of characteristic peaks (f) of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 2. Figure 3 As can be seen from the ab part, the maximum lateral dimension of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 can reach 163 μm, and has an ultra-thin thickness. Figure 3 As can be seen from the middle d part, its thinnest thickness is as low as 0.77nm. Figure 3 The middle part e shows the characteristic peak of β-Bi2O3, which confirms the successful synthesis of β-Bi2O3. -1 The characteristic peaks of the Raman scan are shown in the following figure. Figure 3 As shown in part f, the signal intensity distribution is uniform across the entire sample area, confirming that the synthesized β-Bi2O3 flakes are of high quality.
[0061] Figure 4 The high-angle annular dark-field scanning transmission electron microscopy image of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 (a), the enlarged view of Figure a (b), the intensity line profile extracted from the white dashed box in Figure b (c), the selected area electron diffraction pattern of the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 (d), the atomic model of the β-Bi2O3 crystal along the (100) direction (e), the adsorption energy of Se atoms on different surfaces of β-Bi2O3 (f), and the adsorption energy of Se atoms from the internal bulk phase of β-Bi2O3 to the surface atomic layer (gh). Figure 4 It can be seen from part a that the two-dimensional ultrathin non-layered material β-Bi2O3 prepared in Example 1 presents a highly ordered atomic structure arrangement and no obvious defects exist, which proves that the synthesized Bi2O3 crystals have high crystallization quality. The measured lattice spacings are 0.77nm and 0.58nm, corresponding to the (010) and (001) crystal planes of β-Bi2O3, respectively. Figure 4 Part b further presents an enlarged high-angle annular dark-field scanning transmission electron microscopy image, which is similar to Figure 4 Part e in the middle is consistent with the crystal structure model observed from the (100) direction of Bi2O3. Figure 4 The red box in b is a typical unit cell, which is also Figure 4 The unit cell in e fits perfectly. Figure 4Part c clearly presents the consistent intensity of each Bi atomic column, confirming that the synthesized β-Bi2O3 is of high quality and excellent uniformity. Figure 4 The selected area electron diffraction pattern in part (d) shows a single set of diffraction spots, which is consistent with the lattice characteristics of β-Bi2O3 and confirms the single crystal characteristics of the synthesized β-Bi2O3. Figure 4 Part f shows the adsorption energy of Se on the (100), (011) and (111) surfaces of β-Bi2O3 crystals. Se atoms preferentially bond with unsaturated Bi atoms to form Bi-Se order. The adsorption energy of Se on the (100) surface is 0.30 eV, while the adsorption energies of Se on the (011) and (111) surfaces are 1.11 eV and 1.54 eV, respectively. By comparison, it is found that the adsorption energy of Se on the (100) surface is significantly lower. Figure 4 It can be seen from the middle gh part that for the (100) plane, the adsorption energy of Se atoms from the internal bulk phase of β-Bi2O3 to the surface atomic layer gradually decreases. These results all prove that Se atoms preferentially adsorb on the (100) surface of β-Bi2O3 and occupy surface sites, thereby inhibiting the growth in the vertical direction and promoting the growth of ultrathin β-Bi2O3.
[0062] Example 2
[0063] The difference from Example 1 is that in step S5, the crystal growth is carried out at 700° C. for 60 minutes, and the remaining steps are the same as Example 1.
[0064] Figure 3 Part c in the figure is an optical microscope image of the two-dimensional ultrathin non-layered material β-Bi2O3 prepared in Example 2. It can be seen that under the condition that the crystal growth time is 60 min, a large-area β-Bi2O3 crystal can be obtained.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that the Bi2Se3 sheet is omitted, and the remaining steps are the same as Example 1.
[0067] Comparative Example 2
[0068] The difference from Example 1 is that in step S3, 60 mg Bi2O3 powder and 60 mg Bi2Se3 flakes are weighed, and the remaining steps are the same as Example 1.
[0069] Comparative Example 3
[0070] The difference from Example 1 is that in step S3, 60 mg Bi2O3 powder and 20 mg Bi2Se3 flakes are weighed, and the remaining steps are the same as Example 1.
[0071] Figure 5The optical microscope images of β-Bi2O3 prepared in Example 1 and Comparative Examples 1-3, wherein a is Comparative Example 1 (Bi2O3:Bi2Se3=1:0), b is Comparative Example 2 (Bi2O3:Bi2Se3=1:1), c is Example 1 (Bi2O3:Bi2Se3=2:1), and d is Comparative Example 3 (Bi2O3:Bi2Se3=3:1). Figure 5 As can be seen from part a in the figure, without adding the auxiliary agent Bi2Se3, the obtained β-Bi2O3 has a large thickness. Figure 5 As can be seen in part b, when the mass ratio of Bi2O3 to Bi2Se3 is 1:1, irregular dots are grown, and no 2D β-Bi2O3 product is synthesized. Figure 5 As can be seen from part d, when the mass ratio of Bi2O3 to Bi2Se3 is 3:1, the grown β-Bi2O3 has a large thickness, and it is difficult to synthesize β-Bi2O3 with ultra-thin thickness.
[0072] Example 3
[0073] The two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 is made into a photodetector. The structure of the photodetector is shown in FIG. Figure 6 In a, the specific preparation process is as follows: the device is prepared based on the two-dimensional ultra-thin non-layered material β-Bi2O3 synthesized in Example 1, and electrodes formed by 10nm thick Cr and 30nm thick Au are transferred to β-Bi2O3 as source electrode and drain electrode by means of transfer electrode, and light with a wavelength of 365nm is used as the light source to obtain a photodetector.
[0074] The photodetector prepared in Example 3 was tested for electrical and photoelectric properties using a probe station. Figure 6 . Figure 6 Schematic diagram of the structure of the photodetector prepared in Example 3 (a), IV curves under different light intensities (b), intensity-dependent responsivity and detectivity (c), EQE under different light intensities (d), IT curves under light of different wavelengths (e) and characteristic light response time curve in fast scanning mode (f). Figure 6 Part b is under 365nm light, the light power is from 0.022mW·cm -2 To 2.15mW·cm -2 The power dependence of the photodetector was studied in the range of 200 Å and 800 Å. The results show that the photocurrent increases significantly with the increase of light intensity. Figure 6 As can be seen from part c, the maximum responsivity and detection rate of the photodetector prepared in Example 3 can reach 47.44A·W -1 and 3.29×10 14 Jones. By Figure 6 As can be seen from the middle d part, its maximum EQE can reach 1.6×10 4 %.Depend on Figure 6 As can be seen from part e, after multiple cycles, the photocurrent shows periodic repetition without obvious deviation, proving that the device has excellent stability and repeatability. Figure 6 As can be seen from the middle f part, the rise time of the device is 10ms and the fall time is 12ms, indicating that the device has a fast light response process. In short, the above device indicators all show that the performance of this photodetector is better than most photodetectors based on two-dimensional materials.
[0075] Example 4
[0076] The two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 is made into a polarization-sensitive photodetector. The structure of the photodetector is shown in FIG. Figure 7 In a, the specific preparation process is: based on the two-dimensional ultra-thin non-layered material β-Bi2O3 synthesized in Example 1, electrodes formed by 10nm thick Cr and 30nm thick Au are transferred to β-Bi2O3 as source electrode and drain electrode by means of transfer electrode, light with a wavelength of 365nm is used as the light source, and a half-wave plate is placed above the light source to change the direction of the light source, thereby obtaining a polarization-sensitive photodetector.
[0077] The polarization-sensitive photodetector prepared in Example 4 was tested electrically and photoelectrically using a probe station. The direction of the laser beam was changed by rotating the half-wave plate. The results are shown in Figure 7 . Figure 7 The schematic diagram of the structure of the polarization-sensitive photodetector prepared in Example 4 (a), the IV curve under periodic change of polarization angle (b), the polarization-dependent photocurrent polar coordinate diagram (c), and the polarization-dependent responsivity polar coordinate diagram (d). Figure 7 As can be seen from part b, when the direction of the laser beam changes periodically over time, a periodically changing photocurrent will be generated. Figure 7 Extract the data from part b of the diagram and plot the polarization-dependent photocurrent and responsivity in polar coordinates, as shown in Figure 7 As shown in the cd part. Figure 7 The middle cd part shows that the photocurrent and responsivity change periodically with the rotation angle, with maximum values at 90° and 270° and minimum values at 0° and 180°. The calculated anisotropy ratio of photocurrent to responsivity is 1.91. The above results show that the two-dimensional ultra-thin non-layered material β-Bi2O3 prepared in Example 1 has strong in-plane photoelectric anisotropy, providing an ideal platform for multifunctional optoelectronic devices.
[0078] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A surface passivation-assisted growth method for two-dimensional ultra-thin non-layered material β-Bi2O3, characterized in that: The following steps are involved: Using Bi2O3 as a precursor and Bi2Se3 as an auxiliary agent, Bi2O3 and Bi2Se3 are placed at the heat source center and upstream of a tube furnace respectively, and fluorphlogopite is placed directly above Bi2O3. The temperature is then raised to the growth temperature for crystal growth, and then cooled to room temperature to obtain a two-dimensional ultra-thin non-layered material β-Bi2O3. The mass ratio of Bi2O3 to Bi2Se3 is 2:
1.
2. The surface passivation assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 according to claim 1, characterized in that: The distance between the fluorophlogopite and Bi2O3 is 4 mm.
3. The surface passivation assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 according to claim 1, characterized in that: The fluorophlogopite mica further comprises a pre-treatment step before use; the pre-treatment method is: peeling the fluorophlogopite mica and using the freshly dissociated surface as the crystal growth surface.
4. The surface passivation assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 according to claim 1, characterized in that: The growth temperature is 680-750°C.
5. The surface passivation assisted growth method of two-dimensional ultra-thin non-layered material β-Bi2O3 according to claim 1, characterized in that: The crystal growth time is 20-60 minutes.
6. A two-dimensional ultra-thin non-layered material β-Bi2O3 obtained by the surface passivation assisted growth method of the two-dimensional ultra-thin non-layered material β-Bi2O3 as described in any one of claims 1 to 5.
7. The two-dimensional ultra-thin non-layered material β-Bi2O3 according to claim 6, characterized in that: The thinnest thickness of the two-dimensional ultra-thin non-layered material β-Bi2O3 is 0.77nm, and the maximum lateral size is 163μm.
8. Application of the two-dimensional ultra-thin non-layered material β-Bi2O3 according to any one of claims 6 to 7 in the field of optoelectronics.
Citation Information
Patent Citations
Method for preparing two-dimensional non-layered wide-band-gap oxide based on Van der Waals epitaxy
CN115287750A